Orthostatic change in blood pressure and incidence of atrial fibrillation: results from a bi-ethnic population based study. - Sunil K Agarwal; Alvaro Alonso; Seamus P Whelton; Elsayed Z Soliman; Kathryn M Rose; Alanna M Chamberlain; Ross J Simpson; Josef Coresh; Gerardo Heiss (PLoS ONE)
Background Autonomic fluctuations are associated with the initiation and possibly maintenance of atrial fibrillation (AF). However, little is known about the relationship between orthostatic blood pressure change, a common manifestation of autonomic dysfunction, and incident AF. Methods We examined whether supine-to-standing changes in systolic blood pressure (SBP) are associated with incident AF in 12,071 African American and white men and women aged 45-64 years, enrolled in the Atherosclerosis Risks in Communities (ARIC) study. Orthostatic hypotension (OH) was defined as a supine-standing drop in SBP by ≥20 mmHg or diastolic blood pressure by ≥10 mmHg. AF cases were identified based on study scheduled 12-lead ECG, hospital discharge ICD codes, and death certificates through 2009. Results OH was seen in 603 (5%) at baseline. During an average follow-up of 18.1 years, 1438 (11.9%) study participants developed AF. Incident AF occurred more commonly among those with OH than those without, a rate of 9.3 vs. 6.3 per 1000 person years, (p<0.001). The age, gender, and race adjusted hazard ratio (95%CI) of AF among those with OH compared to those without was 1.62 (1.34, 2.14). This association was attenuated after adjustment for common AF risk factors to HR 1.40 (1.15, 1.71), a strength similar to that of diabetes or hypertension with AF in the same model. A non-linear relationship between orthostatic change in SBP and incident AF was present after multivariable adjustment. Conclusions OH is associated with higher AF incidence. Whether interventions that decrease OH can reduce AF risk remains unknown.